Training needs for heads of scientific departments In the colleges of Al-Mustansiriya University (Journal of the College of Basic Education, 2024)
Determining training needs is the first starting point for developing human capacities and skills in order to improve individual, organizational and societal performance. Considering that the overall administrative and organizational performance of the college system depends to a high degree on the performance of those in charge of the responsibility of heading the scientific departments, this strongly claims for an organized periodic review of their needs related to the organizational work .The current research aimed to survey the training needs of the heads of scientific departments in the colleges of Al - Mustansiriya University, and in that it followed the Descriptive method, and stratified random sample was adopted in selecting the sample members by a percentage (18%) of the total members of the current research community. After applying the questionnaire that prepared for the purposes of the current research and using the t-test and the "Fisher" equation as statistical means in data processing, the researcher found that the cognitive needs (non-stereotypical) were at the forefront of the needs of the heads of scientific departments, and that all the skills of heads of scientific departments (related to their administrative work ) was within the low limits.The most prominent recommended by the researcher (necessity heads of the scientific departments to reach the limits of clear awareness regarding the university's philosophy and the college's instructions and goals). And his most prominent suggestions (a model of administrative development for heads of scientific departments according to the Empowerment Department).